Analysis of Work Discipline and Work Environment on Human Resource Development at the Ministry of Religion through Work Motivation - Qaulan Shadida; Sri Rahayu (International Journal of Management, Economic and Accounting, 2024)
This research aimed to examine the direct and indirect effects of work discipline and work environment on HR development through work motivation. The research was conducted at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province in 2024. The subjects of this research were all 258 Civil Servant employees (ASN) at the Regional Office of the Ministry of Religious Affairs of North Sumatra, consisting of 185 civil servants and 73 PPPK (non-permanent government employees). A sample size of 72 ASN employees was determined using Slovin’s formula, and a purposive sampling technique was applied. The data type used was primary-quantitative data, collected through questionnaire distribution. The research used an associative-quantitative approach with SEM-PLS (Structural Equation Modeling - Partial Least Squares) analysis technique. Data from the questionnaire responses were processed using the SmartPLS 3 application. The findings indicated that work discipline and work environment had a direct, positive, and significant impact on work motivation and HR development, thus proving and accepting Hypotheses H1, H2, H3, and H4. Work discipline was the most influential variable on work motivation and HR development. Directly, work motivation had no significant effect on HR development, so Hypothesis H5 was rejected and unproven. Work discipline and work environment indirectly through work motivation also had no significant impact on HR development, thus rejecting and disproving Hypotheses H6 and H7. Work Discipline (X1) and Work Environment (X2) contributed to or explained 69.0% of the formation of the Work Motivation (Z) variable. Meanwhile, Work Discipline (X1), Work Environment (X2), and Work Motivation (Z) contributed to or explained 73.5% of the formation of the HR Development (Y) variable.